Synthesis of paenipeptin C′ analogues employing solution-phase CLipPA chemistry. Issue 23 (29th May 2020) - Tong, Juliana T. W.; Kavianinia, Iman; Ferguson, Scott A.; Cook, Gregory M.; Harris, Paul W. R.; Brimble, Margaret A.
Abstract : Thiol–ene CLipPA reaction of a vinyl ester and thiolated peptide for generation of an S -lipidated paenipeptin C′ analogue with broad spectrum antibacterial activity. Abstract : We herein report the synthesis of analogues of the antimicrobial lipopeptide, paenipeptin C′, by installing varying lipid moieties using thiol–ene CLipPA (Cysteine Lipidation on a Peptide or Amino Acid) chemistry. Biological evaluation against both Gram-negative and Gram-positive strains indicated that several analogues possessed potent broad-spectrum antimicrobial activity.